Survei Keterampilan Teknik Dasar Lay Up Dan One Hand Set Shot Pada Siswa Peserta Ekstrakurikuler Bolabasket Sekolah Menengah Atas - Pratama, Kharisma Yudha Eka; Wahyudi, Usman; Fitriady, Gema (Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to determine the level of basic technical skills of lay up and one hand set shot of basketball extracurricular members at SMAN 1 Turen Malang Regency. This research is a quantitative descriptive study using a survey method. The research subjects were 20 participants. The data analysis technique in this study used the percentage formula. The results showed that the extracurricular participants did the lay up and one hand set shot skills test in the